THE EFFECT OF SUBMERGED BREAKWATER ON RESONANCE PHENOMENON IN DIFFERENT TYPES OF BASIN - Mayandel Valerio, Richie
The phenomenon of wave oscillation is caused by external forces on a basin. When the period of the external force is equal to the basin’s natural period, the body of water may experience resonance. If left unchecked for too long, this phenomenon can cause damage to the surrounding area, especially the coastal area. An effort that can be made to minimize the resonance phenomenon is to add a breakwater at the bottom of the basin. Previous studies have examined the impact of submerged breakwaters on semi-closed basins with a rectangular width. In this research, the basins of interest are a semi-closed basin with a triangular width and constant depth and a semi-closed basin with a triangular width and a triangular depth, to which is added one block of the submerged breakwater with a smooth and rough surface. In each type of basin, the value of the analytical natural period is found using the modified shallow water equations. Then, numerical simulations are carried out to check the presence of resonance phenomena in each basin. For the basin added with rough-surfaced submerged breakwater, the optimum friction coefficient that can prevent the phenomenon of resonance from occurring will also be investigated. The results of this study indicate that adding one block of the smooth-surfaced submerged breakwater is not enough to stop the resonance phenomenon. On the other hand, the resonance can be stopped at each basin by increasing the friction coefficient of the submerged breakwater.